Thermodynamic analysis and multi objective optimization of performance of solar dish Stirling engine by the centrality of entransy and entropy generation. (June 2016) - Ahmadi, Mohammad Hossein; Ahmadi, Mohammad Ali; Mellit, Adel; Pourfayaz, Fathollah; Feidt, Michel
Highlights: Thermodynamic analysis of solar dish Stirling engine is performed. The latter is achieved using NSGA II algorithm. The final optimal solution has been selected using three decision-making methods. Error analysis was performed based on the average error and the maximum error. Abstract: This paper makes attempts to perform multi-objective optimization on the solar-powered Stirling engine with high temperature differential. A new model was proposed based on the finite-time thermodynamic. Furthermore, the thermal efficiency of the solar Stirling system with a rate of finite heat transfer, regenerative heat loss, the output power, finite regeneration process time and conductive thermal bridging loss is specified. The thermal efficiency, entransy loss rate and power output have been maximized simultaneously for a dish-Stirling system and entropy generation's rate in the engine minimized via using thermodynamic analysis and NSGA-II algorithm. To specify the optimum values of the above mentioned parameters three well known decision making methods have been employed. Finally, an error analysis was applied on the outputs gained from each decision makers.